Convergence of Inflammatory Pathways in Allergic Asthma and Sickle Cell Disease - Samarasinghe, Amali E.; Rosch, Jason W. (Frontiers in Immunology, 2020)
The underlying pathologies of sickle cell disease and asthma share many characteristics in terms of respiratory inflammation. The mechanisms underlying the pulmonary inflammation are largely distinct but activation of common pathways downstream of the initial inflammatory triggers could lead to exacerbation of both disease states. The altered inflammatory landscape underlying these respiratory pathologies can have differing impact on susceptible to respiratory pathogens. How these two distinct diseases behave in a comorbid state can further exacerbate pulmonary complications associated with both disease states and impact susceptibility to respiratory infection. In this review will provide a concise overview of the how asthma distinctly impacts individuals with sickle cell disease and how this comorbid condition impacts both disease states in terms of respiratory disease and inflammation.